ECG quality assessment using neural network trained with synthetic data - Vasankari, Antti (My University, 2024)
An electrocardiogram (ECG), is a common, safe, and simple way to examine the electrical activity of the heart as a signal over time, from which heart rate can be measured and heart diseases can be detected. ECG is susceptible to interference, so it is important that the quality of the signal is sufficient for the feature being examined. The quality of the ECG should reflect its usability, and the quality assessment should be consistent. Manual signal quality assessment is laborious and depends on the annotators expertise. Training machine learning models for this task requires large amounts of quality-labeled sensitive health data. Additionally, the generalizability of the model is decreased due to the inability to distinguish the noise from the pure signal. This master's thesis presents a method, in which a quality classifier was added to a modular synthetic ECG generator. The labeled synthetic data was then used for training a simple convolutional neural network. Additionally, methods to improve the representativeness of the quality-labeled synthetic data was examined. The validation and test data consisted of manually labeled real-world single-lead ECG measurements. The performances of the models, trained on synthetic data, were compared with a model of the same architecture that was trained on the validation data. The results support the utility of the synthetic ECG signals for training a quality assessor. Augmenting the training data with synthetic data improved the classification performance of the model trained on validation data. Furthermore, the flexibility of the synthetic ECG generator enables the customization of quality criteria and domain randomization, which, based on the results, appear to be beneficial methods.

Elektrokardiogrammi (EKG), eli sydänfilmi on yleinen, turvallinen ja yksinkertainen tapa tutkia sydämen sähköistä toimintaa ajan signaalina, josta voi mitata sykettä ja havaita sydänsairauksia. EKG on altis häiriöille, ja täten tulkinnassa on tärkeää, että signaalin laatu on tarkasteltavan ominaisuuden kannalta riittävän hyvä. EKG:n laadun tulisi heijastaa sen käyttökelpoisuutta, ja laadun luokittelun tulisi olla johdonmukaista. Manuaalisesti signaalien laadun luokittelu on työlästä sekä riippuvaista luokittelijan osaamisesta. Koneoppimismallien kouluttaminen tehtävään vaatii suuria määriä laatuluokiteltua sensitiivistä terveysdataa, ja lisäksi näiden mallien koulutuksessa esiintyy aineiston aiheuttamaa vinoumaa, koska laatua heikentävä kohina ei ole eristettävissä kohisevasta signaalista. Tässä pro gradu -tutkielmassa esitetään menelmä, jossa modulaariseen synteettisen EKG:n generaattoriin lisättiin generoidun signaalin laatuluokittelija. Tätä laatuluokiteltua synteettistä dataa hyödynnettiin yksinkertaisen konvoluutioneuroverkon koulutuksessa. Lisäksi tarkasteltiin synteettisen datan laatuluokkien edustavuuden parantamista. Validointi- ja testidatana käytettiin manuaalisesti luokiteltuja todellisia yksikytkentäisiä EKG-mittauksia. Koulutettujen mallien luokittelukykyä vertailtiin saman arkkitehtuurin malliin, joka koulutettiin validointidatalla. Tulokset tukevat synteettisen EKG:n käyttökelpoisuutta laatuluokittelijan koulutusaineistona. Synteettisen aineiston käyttö paransi mallin luokittelukykyä. Lisäksi synteettisen EKG:n generaattorin joustavuus mahdollistaa laatukriteerin muokattavuuden ja koulutusaineiston rikastamisen, jotka tulosten perusteella vaikuttavat hyödyllisiltä menetelmiltä.
Keywords: ECG, electrocardiogram, synthetic data, signal quality assessment, SQA, machine learning, ML, health technology